TEOLOGI ETIS TERHADAP PENDIDIKAN YANG MEMERDEKAKAN DIPERHADAPKAN DENGAN PENGAJARAN JOHN WESLEY - Meldayana Harianja (Majalah Ilmiah METHODA, 2024)
Education is an effort to foster and guide "all aspects" inherent in humanity. Every person wants to be independent because he wants to interpret his existence as a civilized (independent) human being. So that humans can be independent and free from all shackles to become humane people, one of the strongest efforts is through education. However, the reality is that until now education has not been able to reach its ideal point, namely humanizing humans so that they become fully human, what has happened is the opposite, namely increasing the level and dignity of humans. The theology of independence, which is an accountability of faith as well as practice in a crisis of society with a spirit of independence. A spirit of freedom inspired by the realization of the Kingdom of God in fighting injustice and taking sides for the poor and oppressed for the good and salvation of all people. Worship of God must also be manifested in concern for humans.